Applicability and usefulness of pupillometry in the study of lexical access. A scoping review of primary research - Rojas, Carlos; Vega-Rodríguez, Yuri E.; Lagos, Gabriel; Cabrera-Miguieles, María Gabriela; Sandoval, Yasna; Crisosto-Alarcón, Jaime (Frontiers in Psychology, 2024)
Pupil dilation has been associated with the effort required to perform various cognitive tasks. At the lexical level, some studies suggest that this neurophysiological measure would provide objective, real-time information during word processing and lexical access. However, due to the scarcity and incipient advancement of this line of research, its applicability, use, and sensitivity are not entirely clear. This scoping review aims to determine the applicability and usefulness of pupillometry in the study of lexical access by providing an up-to-date overview of research in this area. Following the PRISMA protocol, 16 articles were included in this review. The results show that pupillometry is a highly applicable, useful, and sensitive method for assessing lexical skills of word recognition, word retrieval, and semantic activation. Moreover, it easily fits into traditional research paradigms and methods in the field. Because it is a non-invasive, objective, and automated procedure, it can be applied to any population or age group. However, the emerging development of this specific area of research and the methodological diversity observed in the included studies do not yet allow for definitive conclusions in this area, which in turn does not allow for meta-analyses or fully conclusive statements about what the pupil response actually reflects when processing words. Standardized pupillary recording and analysis methods need to be defined to generate more accurate, replicable research designs with more reliable results to strengthen this line of research.